Picture imperfect Utopian thought for an anti-Utopian age - Jacoby, Russell (Columbia Univ. Press, 2005)
"Writing against the grain of history, Russell Jacoby reexamines the anti-utopian mindset and identifies how utopian thought came to be regarded with great suspicion. He offers stinging critiques of the influential liberal and anti-utopian theorists Hannah Arendt, Isaiah Berlin, and Karl Popper, arguing that these thinkers mistakenly equate utopianism with totalitarianism."--BOOK JACKET.